Expert evaluation of the lower limb function of hip fracture outcomes. - Sokol, V. K. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. In patients with fractures of the femur in 4-26% of the cases develop complications (nonunion or delayed consolidation of the fracture, preservation of residual deformities of the femur, the formation of persistent post-traumatic contractures of adjacent joints), which can lead to prolonged temporary or permanent disability. Objective. To evaluate the function of the lower extremities in patients with outcome of fractures of the femur using the method of statography. Methods. The material of the study was protocols of clinical and radiological examination of 33 patients with fused fracture and residual deformities of the femoral diaphysis. Research methods: orthopedic (measuring the length of both lower limbs and the strength of their muscles, and circumference of soft tissues of thighs and shins), radiologic (plain radiography in two standard projections), biomechanical (using the platform statograph), statistical. Results. Closed (90.9%) oblique (78.7%) fractures of the femur prevailed, most often (63.8%) located in the middle third of the diaphysis. All patients underwent surgical treatment, the most frequent complication of which was delayed consolidation of fragments of the femur (54.5%), shortening of the lower limb on the fracture side (69.7%). Results. Closed (90.9%) oblique (78.7%) fractures of the femur prevailed, most often (63.8%) located in the middle third of the diaphysis. All patients underwent surgical treatment, the most frequent complication of which was delayed consolidation of fragments of the femur (54.5%), shortening of the lower limb on the fracture side (69.7%). The results of the statography made it possible to establish that in the case of a unilateral standing on the damaged leg compared to a healthy leg, a significant (p <0.05) increase in the body swing amplitude, a decrease in load and stability factors (p <0.05), and a displacement of the projection of the gravity line in the sagittal and frontal planes. Conclusion. The data obtained in combination with the detected hypotrophy and reduced muscle strength of the injured lower limb indirectly indicate a decrease in the support function of the leg with residual post-traumatic deformity of the shaft of the femur.